The Revised Statutes of the State of Florida 782-83 (W.A. Blount et al. eds., 1892) - (:unkn) unknown (My University, 1868)
1868 Fla. Rev. Stat., tit. 2, art. 5, § 2423: Enhanced the sentence of anyone concealed carrying slung-shot, metallic knuckles, billies, firearms, or other dangerous weapons while committing a criminal offense or breaching the peace. Violators fined not exceeding fifty dollars or imprisonment not exceeding one year.
Keywords: CARRY - INTENT TO COMMIT CRIME